2018
DOI: 10.11648/j.ijnfs.20180703.12
|View full text |Cite
|
Sign up to set email alerts
|

Junk Food Consumption and Its Association with Body Mass Index Among School Adolescents

Abstract: Healthy and nutritious food are being replaced by new commercial food items called Junk Food. These food item are with high calories but with low nutritive values. Excess consumption of junk food is associated with several nutritional problems ranging from underweight to obesity and various Non-communicable diseases. The study was conducted to assess the general junk food consumption habits, pattern and its association with Body Mass Index among adolescents. A descriptive cross sectional design was adopted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 2 publications
4
7
1
Order By: Relevance
“…Junk food consumption is significantly associated with malnutrition or low BMI among adolescents [18]. This result is consistent with the findings of the present study, in which children who ate junk food are at increased risk of having low BMI.…”
Section: Discussionsupporting
confidence: 93%
“…Junk food consumption is significantly associated with malnutrition or low BMI among adolescents [18]. This result is consistent with the findings of the present study, in which children who ate junk food are at increased risk of having low BMI.…”
Section: Discussionsupporting
confidence: 93%
“…The Nepali population's dietary patterns have also changed over the past 40 years (Subedi et al, 2017). As elsewhere, junk food consumption has become commonplace among schoolchildren in Nepal (Neupane, 2014;Poudel, 2018;Poudel et al, 2018;Sapkota and Neupane, 2017). Junk food may be attractive to schoolchildren because it provides quick energy, tastes good, is easily accessible, is portable, and saves parents' time to prepare (Arya and Mishra, 2013;Kotecha et al, 2013;Vaida, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have implicated consumption of junk foods as substitutes to nutritious healthy diets as causes of overweight and obesity [25,26]. Overweight and obesity are risk factors for many diseases and the increase in its incidence among the young adults' population is worrisome [24,33]. In Nigeria, junk food is commonly consumed among students because of its availability and accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that availability and accessibility of junk food at various points in the country especially at educational institutions has significantly increased over the years [24,25]. This has led to the increase in the number of students adopting the consumption of unhealthy junk food instead of nutritious healthy diets [24,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation